2016
DOI: 10.1016/j.jallcom.2016.01.185
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of barium ferrate(VI): Mechanism and formation of FeIV intermediate and nanocrystalline Fe2O3 and ferrite

Abstract: Simple high-valent iron-oxo species, ferrate(VI) (Fe VI O 2-4 , Fe(VI)) has applications in energy storage, organic synthesis, and water purification. Of the various salts of Fe(VI), barium ferrate(VI) (BaFeO 4) has also a great potential as a battery material. This paper presents the thermal decomposition of BaFeO 4 in static air and nitrogen atmosphere, monitored by combination of thermal analysis, Mössbauer spectroscopy, X-ray powder diffraction, and electron-microscopic techniques. The formation of Fe IV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Moreover, the existence of magnetic sextets in Mössbauer spectra indicated that the Néel temperature (T N ) of BaFeO 3 -Cop and BaFeO 3 -Sol samples is above the room temperature [29,30]. This result is agreement with previous reports for barium ferrate and Ba 1-x Ca x FeO 3 (where x=0.05) as well as it is consistent with the following magnetic measurement of the BaFeO 3 -Sol and BaFeO 3 -Cop samples [31,32]. The single peak and quadrupole doublet in the Mössbauer spectra of BaFeO 3 -Cop and BaFeO 3 -Sol samples (Fig.…”
Section: Xrd Sem and Dls Studiessupporting
confidence: 92%
“…Moreover, the existence of magnetic sextets in Mössbauer spectra indicated that the Néel temperature (T N ) of BaFeO 3 -Cop and BaFeO 3 -Sol samples is above the room temperature [29,30]. This result is agreement with previous reports for barium ferrate and Ba 1-x Ca x FeO 3 (where x=0.05) as well as it is consistent with the following magnetic measurement of the BaFeO 3 -Sol and BaFeO 3 -Cop samples [31,32]. The single peak and quadrupole doublet in the Mössbauer spectra of BaFeO 3 -Cop and BaFeO 3 -Sol samples (Fig.…”
Section: Xrd Sem and Dls Studiessupporting
confidence: 92%
“…Overall, the technique to identify directly Fe IV /Fe V species in the Fe VI –micropollutant systems under aqueous solutions remains elusive. However, the investigation of decomposition of solid Fe VI using Mossbauer spectroscopy has shown Fe IV as the intermediate species. , We have therefore applied a kinetic modeling approach to assess which of the two species, that is, Fe V and Fe IV , caused the enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…However, the investigation of decomposition of solid Fe VI using Mossbauer spectroscopy has shown Fe IV as the intermediate species. 37,55 We have therefore applied a kinetic modeling approach to assess which of the two species, that is, Fe V and Fe IV , caused the enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mössbauer technique is suitable for solid samples and requires a certain amount of iron content in order to observe the spectrum of iron. Studies on ferrates using Mössbauer spectroscopy are largely limited to solid state chemistry. , Incorporation of 57 Fe into solid K 2 FeO 4 samples has been applied to minimize the required iron content for Mössbauer measurements. ,, Investigations on ferrates in solution require rapid freezing of the liquid to obtain solid samples prior to performing Mössbauer spectroscopy measurements (i.e., frozen solution) . In addition to the minimum iron content, the time required to freeze the liquid is another constraint that limits observations of the change in the iron oxidation state of ferrate during a short time scale.…”
Section: Experimental Approaches To Identify Iron Intermediatesmentioning
confidence: 99%